2010
DOI: 10.3130/jaabe.9.215
|View full text |Cite
|
Sign up to set email alerts
|

Urban Disaster Prevention Shelter Location and Evacuation Behavior Analysis

Abstract: This study proposes a simple method of analyzing the road network factors and evacuation choices of residents in case of an earthquake. Using questionnaire survey data from Shin-Hua, Tainan County Taiwan, this study uses 6 indexes to evaluate shelter safety and applies a spatial statistic model with Local Indicators of Spatial Association (LISA) as an index to the evacuation choice of residents. Firstly, factor analysis is used to find the key factors affecting shelter safety, and cluster analysis is used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Additional knowledge on population dynamics, as in Freire and Aubrecht (2012) might, be beneficial for a more detailed study. Optionally, remote sensing has shown advantages in assessing the urban fabric and population distribution in larger agglomerations (e.g., Aubrecht et al, 2013;Kubanek et al, 2010;Taubenböck, 2008). Some key numbers and characteristics of the data used in this exemplary case study can be found in Table 3.…”
Section: Case Study Kathmandu Metropolitan Citymentioning
confidence: 99%
See 3 more Smart Citations
“…Additional knowledge on population dynamics, as in Freire and Aubrecht (2012) might, be beneficial for a more detailed study. Optionally, remote sensing has shown advantages in assessing the urban fabric and population distribution in larger agglomerations (e.g., Aubrecht et al, 2013;Kubanek et al, 2010;Taubenböck, 2008). Some key numbers and characteristics of the data used in this exemplary case study can be found in Table 3.…”
Section: Case Study Kathmandu Metropolitan Citymentioning
confidence: 99%
“…People seeking shelter rely on some sort of existing and suitable network (roads) to access available shelter areas within a certain time (Tai et al, 2010). Kongsomsaksakul et al (2005) use a two-level mathematical representation to show authorities' selections of best-suited evacuation sites on the one hand and evacuees' decisions on the escape route to that determined site on the other hand.…”
Section: Accessibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys have been conducted to analyze residents' perceptions of volcanic hazards [5], to clarify the risks of and reasons for evacuation [6], and to assess tourists' perceptions of hurricanes, based on forecasts [7]. Algorithms and programming methods were created to generalize optimal evacuation plans (e.g., models used to analyze building evacuability [8], to develop mathematical modeling to simulate evacuation problems [9], to develop GIS-based mapping of evacuation choices during earthquakes [10], to develop a new multiagent system (SimTread) that calculates the shortest walking times [11], and to develop an evacuation simulator [12]). Studies have evaluated evacuation times to determine optimal routes.…”
Section: Literature Reviewmentioning
confidence: 99%